2022
DOI: 10.1158/1538-7445.am2022-lb522
|View full text |Cite
|
Sign up to set email alerts
|

Abstract LB522: Fibroblast activation protein triggers the release of drug payload from non-internalizing small molecule-drug conjugates in solid tumors

Abstract: Small Molecule-Drug Conjugates (SMDCs) are modular anti-cancer pro-drugs that include a tumor-targeting small ligand, a cleavable linker and a potent cytotoxic agent. SMDC products that have been developed for clinical applications are targeting internalizing tumor-associated antigens expressed on the surface of tumor cells. We have recently developed a novel non-internalizing small organic ligand (named OncoFAP) of Fibroblast Activation Protein (FAP), a tumor-associated antigen highly expressed in the stroma … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…SMDCs are usually composed of targeted molecules, linkers and effector molecules [320]. In fact, due to the excessive segmentation in the field of drug conjugates, there is also crossover between different drug concepts, and PDCs are examples of SMDCs.…”
Section: Small-molecule-drug Conjugates (Smdcs)mentioning
confidence: 99%
“…SMDCs are usually composed of targeted molecules, linkers and effector molecules [320]. In fact, due to the excessive segmentation in the field of drug conjugates, there is also crossover between different drug concepts, and PDCs are examples of SMDCs.…”
Section: Small-molecule-drug Conjugates (Smdcs)mentioning
confidence: 99%
“…In order to investigate the ability of the novel CAIX-targeting ISAC 3 to accumulate in tumors and deliver the immunomodulating R848 payload, ex vivo mass spectrometry-based biodistribution studies in tumor-bearing mice were performed, following a similar protocol reported for MMAE conjugates (Zana et al, 2022) and specifically aimed at i) the detection of the free, released R848 and ii) total antibody quantification, regardless of its chemical functionalization with the linker-drug module. Immunocompetent Balb/c mice bearing subcutaneous CT26.3E10 xenografts (i.e., an orthotopic murine colorectal carcinoma cell line stably transfected with human CAIX) were intravenously injected with 125 nmol/kg of 3, followed by their sacrifice after 6 and 24 h and harvesting of tumor and healthy organs.…”
Section: Ex Vivo Biodistribution Analysismentioning
confidence: 99%
“…Comparison of the efficacy of different conjugates at the same dose showed that SMDC was superior to non-targeted protein conjugates in tumor targeted therapy. 5 SMDCs usually contain a targeting ligand, a spacer, a cleavable bridge, and a therapeutic payload (Figure 1). 6−10 SMDCs' targeting ligands mainly use derivatives of natural sources of ligands such as folic acid derivatives that target folate receptors, glutamic urea derivatives that target prostate specific membrane antigen, and somatostatin analogens that target somatostatin receptors.…”
Section: Introductionmentioning
confidence: 99%